The role of stem cells in the recovery of hemopoiesis in cytostatic and radial myelosuppressions - Ye. D. Goldberg; A. M. Dygai; V. V. Zhdanov (Бюллетень сибирской медицины)
The development of hemopoietic tissue hypoplasia and recovery of hemopoietic dynamics in addition to the direct suppressive effect of toxic agents on hemopoietic cells are mainly due to the character of hemopoietic disregulation were shown on different models of myelosuppressions (irradiation, injecting cytostatic drugs having different action mechanisms). At the same time, compensatory changes of blood system and underlying mechanisms are mainly non-specific and of the same type. Creation of reparative processes in the hemopoietic tissue is significantly by bone marrow stromal cells thanks to chemioand radioresistance of their precursors (mesenchimal stem cells).